Psychological Security and Its relationship With Achievement Motivation In Soccer Players - Mohameed, Mntzr; Mohameed, Mntzr (Journal of Physical Education, 2017)
The importance of the research lies in the lack of psychological security studies and achievement motivation in soccer. Soccer depends on the mental and emotional abilities as well as physical and skill abilities in order to develop the players’ achievement. The players’ individual differences in stimuli responses define the players psychological security for example a situation one soccer player is intimidating and challenging for another. The research aims at identifying the correlation relation between achievement motivation and psychological security. The researcher used the descriptive method. The subjects of the research were (30) soccer players from Al Kurk sport club of the season 2015 – 2016. The results were collected and treated using proper statistical methods to come up with the conclusions. The researcher concluded that all subjects lacked psychological security yet has high levels of achievement motivation. The researcher also concluded that there is an inverse relationship between achievement motivation and psychological security. Finally the researcher recommended that coaches should pay attention to the psychological preparation of players to control their level of psychological security and achievement motivation. In addition to that he recommended using mental training to uplift the players’ psychological security